Clinical and Immunological Phenotype of Patients With Primary Immunodeficiency Due to Damaging Mutations in NFKB2 - Klemann, Christian; Camacho-Ordonez, Nadezhda; Yang, Linlin; Eskandarian, Zoya; Rojas-Restrepo, Jessica L.; Frede, Natalie; Bulashevska, Alla; Heeg, Maximilian; Al-Ddafari, Moudjahed Saleh; Premm, Julian; Seidl, Maximilian; Ammann, Sandra; et al. (Frontiers in Immunology, 2019)
Non-canonical NF-κB-pathway signaling is integral in immunoregulation. Heterozygous mutations in NFKB2 have recently been established as a molecular cause of common variable immunodeficiency (CVID) and DAVID-syndrome, a rare condition combining deficiency of anterior pituitary hormone with CVID. Here, we investigate 15 previously unreported patients with primary immunodeficiency (PID) from eleven unrelated families with heterozygous NFKB2-mutations including eight patients with the common p.Arg853* nonsense mutation and five patients harboring unique novel C-terminal truncating mutations. In addition, we describe the clinical phenotype of two patients with proximal truncating mutations. Cohort analysis extended to all 35 previously published NFKB2-cases revealed occurrence of early-onset PID in 46/50 patients (mean 5.5 yrs, median 2 yrs). ACTH-deficiency occurred in 44%. Three mutation carriers have deceased, four developed malignancies. Only two mutation carriers were clinically asymptomatic. In contrast to typical CVID, most patients suffered from early-onset and severe disease manifestations, including clinical signs of T cell dysfunction e.g. chronic-viral or opportunistic infections. In addition, 80% of patients suffered from autoimmune (AI) phenomena (alopecia > various lymphocytic organ-infiltration > diarrhea > arthritis > AI-cytopenia). Lymphoproliferation was not a hallmark of disease. Immunophenotyping showed largely normal quantities of naïve and memory CD4+ or CD8 + T-cells and normal T-cell proliferation. NK-cell number and function were also normal. In contrast, impaired B-cell differentiation and hypogammaglobinemia were consistent features of NFKB2-associated disease. In addition, an array of lymphocyte subpopulations such as regulatory T cell, Th17-, cTFH-, NKT-, and MAIT-cell numbers were decreased. We conclude that heterozygous damaging mutations in NFKB2 represent a distinct PID entity exceeding the usual clinical spectrum of CVID. Impairment of the non-canonical NF-κB pathways affects function and differentiation of numerous lymphocyte-subpopulations and thus causes a heterogeneous, more severe form of PID phenotype with early-onset. Further characteristic features are multifaceted, primarily T cell-mediated autoimmunity such as alopecia, lymphocytic organ infiltration, and frequently ACTH-deficiency.